Computation-guided scaffold exploration of 2E,6E-1,10-trans/cis-eunicellanes - Li, Zining; Jindani, Sana; Kojasoy, Volga; Ortega, Teresa; Marshall, Erin M.; Abboud, Khalil A.; Loesgen, Sandra; Tantillo, Dean J.; Rudolf, Jeffrey D. (Beilstein Journal of Organic Chemistry, 2024)
Eunicellane diterpenoids are a unique family of natural products containing a foundational 6/10-bicyclic framework and can be divided into two main classes, cis and trans, based on the configurations of their ring fusion at C1 and C10. Previous studies on two bacterial diterpene synthases, Bnd4 and AlbS, revealed that these enzymes form cis- and trans-eunicellane skeletons, respectively. Although the structures of these diterpenes only differed in their configuration at a single position, C1, they displayed distinct chemical and thermal reactivities. Here, we used a combination of quantum chemical calculations and chemical transformations to probe their intrinsic properties, which result in protonation-initiated cyclization, Cope rearrangement, and atropisomerism. Finally, we exploited the reactivity of the trans-eunicellane skeleton to generate a series of 6/6/6 gersemiane-type diterpenes via electrophilic cyclization.
Keywords: atropisomer; Cope rearrangement; DFT calculations; diterpene; electrophilic cyclization; eunicellane